Detection and Preservation of Biosignatures in Mars Analogs Hot Spring Deposits from the Taupo Volcanic Zone, New Zealand - Millan, Maëva (2020)
Characterizing the preservation potential of biosignatures in martian analogs is essential in the quest for biosignatures with martian rovers. Hot spring silica deposits are part of the minerals with a high preservation potential. As part of an ongoing study, we are characterizing the nature and distribution of organic molecules including lipid biomarkers in a range of analog hot spring deposits, evaluating their preservation potential, and determining the potential signals from flight-like experiments. We are focusing on various geothermal fields in the New Zealand Taupo Volcanic Zone with physical and chemical variabilities. Samples are being extracted for lipid biomarker characterization as well as analysis using flight-like experiments from the current and future pyrolyzer-gas chromatographmass spectrometer instruments SAM and MOMA on the Curiosity and Exomars2020 rovers. The aim of work is to improve our knowledge of the detection and preservation of biosignatures in different hot spring lithologies while simultaneously evaluating the potential limits and biases of flight experiments.